Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/polym10111290
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Gelatin Methacryloyl (GelMA) Hydrogels and Their Recent Applications in Load-Bearing Tissue

Abstract: Photocrosslinked gelatin methacryloyl (GelMA) hydrogels have attracted great concern in the biomedical field because of their good biocompatibility and tunable physicochemical properties. Herein, different approaches to synthesize GelMA were introduced, especially, the typical method using UV light to crosslink the gelatin-methacrylic anhydride (MA) precursor was introduced in detail. In addition, the traditional and cutting-edge technologies to characterize the properties of GelMA hydrogels and GelMA prepolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
247
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(249 citation statements)
references
References 106 publications
2
247
0
Order By: Relevance
“…To overcome this challenge, a material with a high swelling ratio is desired for ISF extraction by diffusion. GelMA was selected due to its biocompatibility and composition of primarily gelatin,47 a natural polymer already used in biomedical engineering applications in our previous studies, such as scaffolds,48 injectable hydrogels,49 drugs and growth factor carriers,50 and bioinks for 3D printing 51. We observed that the GelMA had swelling properties promising for the extraction of ISF.…”
Section: Figurementioning
confidence: 99%
“…To overcome this challenge, a material with a high swelling ratio is desired for ISF extraction by diffusion. GelMA was selected due to its biocompatibility and composition of primarily gelatin,47 a natural polymer already used in biomedical engineering applications in our previous studies, such as scaffolds,48 injectable hydrogels,49 drugs and growth factor carriers,50 and bioinks for 3D printing 51. We observed that the GelMA had swelling properties promising for the extraction of ISF.…”
Section: Figurementioning
confidence: 99%
“…When exposed to light, it can be cross‐linked to form a hydrogel with adjustable mechanical properties. GelMA can also be mixed with nanoparticles and other polymers to form a hybrid hydrogel system with specific biological applications (Sun et al, 2018). Some researchers have used GelMA to add ADSCs to repair chronic tendon injuries (Rothrauff et al, 2019).…”
Section: T/l Tissue Engineeringmentioning
confidence: 99%
“…These modified ECMs can then be mixed with cells and crosslinked in the presence of UV light and a photoinitiator [24,25]. The stiffness of the hydrogel can be tuned by varying the UV exposure time and/or intensity, giving way to user-defined physical properties [26]. Some common examples of methacrylate-modified biomaterials are hyaluronic acid and gelatin (HAMA and GelMA, respectively).…”
Section: Influence Of Ecm Stiffness On Neural Fatementioning
confidence: 99%